Effect of realistic 3D microstructure in crystal plasticity finite element analysis of polycrystalline Ti-5Al-2.5Sn. (June 2015) - Zhang, C.; Li, H.; Eisenlohr, P.; Liu, W.; Boehlert, C.J.; Crimp, M.A.; Bieler, T.R.
Abstract: The effect of constitutive parameters and microstructure on the kinematic and constitutive responses within grains in a crystal plasticity finite element (CPFE) simulation of a polycrystalline titanium alloy are compared with experimental results. The simulation of a Ti-5Al-2.5Sn sample deformed in uniaxial tension at room temperature used a phenomenological power-law based CPFE model, which includes four families of slip systems commonly observed in structural metals with a hexagonal lattice structure. The experimentally characterized microstructure patch was approximated by a quasi-3D columnar grain structure and by a more realistic 3D representation. The quasi-3D microstructure was generated by extending the EBSD characterized surface microstructure in the depth direction, while the 3D microstructure was built based on subsurface orientation information acquired using differential-aperture X-ray microscopy (DAXM). The effect of grain morphology and constitutive parameters on simulation results are compared in terms of stress–strain responses and lattice reorientation. Highlights: Comparing crystal plasticity finite element simulation of columnar grain approximation and measured 3D grain structure. Subsurface grain morphology has significant effect on local fields of stress, strain, and crystal reorientation. Agreement between simulated and measured crystal reorientation field improves when respecting subsurface grain morphology.